Agricultural Productivity, Economic Performance, and Environmental Sustainability in Türkiye: Time-Series Evidence from 1992-2022 - Filiz Kutluay Tutar; Abdallah Abukalloub; Nur Funda Tutar; Çisil Erkan Bal (CV. Media Digital Publikasi Indonesia, 2026)
This study examines the relationships among agricultural productivity, input use, irrigation capacity, and sustainability in Türkiye from 1992 to 2022. Annual data from the World Bank were analyzed using descriptive statistics, correlation and multicollinearity tests, unit-root tests, the ARDL bounds-testing approach, robustness analyses, and Granger-causality tests. Separate Newey–West models were estimated for water stress, agricultural N₂O emissions, and agricultural value added per worker. The results indicate a stable long-run relationship in the cereal-productivity model. Fertilizer consumption and agricultural value added per worker are positively and significantly associated with cereal yield, with long-run elasticities of 0.254 and 0.324, respectively. Irrigated land, temperature, and precipitation are statistically insignificant. The error-correction coefficient indicates that approximately 93.5% of deviations from long-run equilibrium are corrected within one year. Granger-causality results indicate predictive precedence from cereal yield to fertilizer consumption, suggesting that reverse causality cannot be excluded. The sustainability models show that fertilizer consumption is positively associated with both agricultural N₂O emissions and agricultural value added per worker in the short run, while the water-stress model yields no significant results. Overall, the findings highlight a productivity–environment trade-off and support policies promoting fertilizer-use efficiency, precision nutrient management, and efficient irrigation.